Utilization of electronic resources in the NDA/BLA regulatory review of bioanalytical data: perspectives from US FDA reviewers. (July 2011) - Au, Stanley; Yu, Chongwoo; Booth, Brian
The electronic common technical document (eCTD) format is frequently used in submitting bioanalytical information as part of a new drug application (NDA) or biologics license application (BLA). While the use of the eCTD format has many advantages, the potential for further improvement exists. This review highlights issues that are commonly encountered in reviewing bioanalytical information during the review process. In addition, the authors suggest potential strategies that illustrate how the ability to locate bioanalytical data or information can be enhanced and the summary information can be more consistently organized for a NDA or a BLA that is submitted in an eCTD format.